Synthesis and Antioxidant Activity of Some Novel Benzimidazole Derivatives - Karmaker, Nilima; Lira, Dilshad Noor; Das, Biplab Kumar; Kumar, Uttom; Rouf, Abu Shara Shamsur (Dhaka University Journal of Pharmaceutical Sciences, 2018)
A series of 2-substituted-5-methylbenzimidazole derivatives (3a-e) were synthesized by reacting 4-methyl-1,2-phenylenediamine (1) with a number of p-substituted benzaldehydes (2a-e) in moderate yields (25.51- 40.21%). The synthesized compounds (3a-e) were characterized by spectroscopic data and were evaluated for antioxidant activity using DPPH free radical scavenging assay. The compounds showed significant antioxidant activity having IC50 value of 1.054-19.05 μg/ml as compared to the standard BHT (26.96 μg/ml). Dhaka Univ. J. Pharm. Sci. 16(2): 245-249, 2017 (December)